Source area and emplacement conditions of Riscos Bayos Ignimbrites, Caviahue-Copahue Volcanic Complex (Argentina) - Haag, Maurício Barcelos (2020)
Fil: Haag, Maurício. Universidade Federal do Rio Grande do Sul. Brasil.